2008
DOI: 10.1007/bf03195243
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant epigenetic patterns in the etiology of gastrointestinal cancers

Abstract: A body of evidence accumulated over the past decade suggests that epigenetic mechanisms play an essential role in maintaining important cellular functions. Changes in epigenetic patterns (mainly DNA hyper- and hypomethylation and, more recently, histone modifications) may contribute to the development of cancer. Aberrant epigenetic events expand thorough tumor progression from the earliest to latest stages, therefore they can serve as convenient markers for detection and prognosis of cancer. The potential reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…Colorectal cancer (CRC) is still the third most common cancer and the second most common cause of cancer-related death worldwide, although considerable progress has been made in the treatment of CRC in recent years12. Thus far, 5-fluorouracil (5-FU) remains a widely used chemotherapeutic drug in the treatment of various cancers, including colorectal carcinoma, breast cancer, gastric cancer and other solid tumors.…”
mentioning
confidence: 99%
“…Colorectal cancer (CRC) is still the third most common cancer and the second most common cause of cancer-related death worldwide, although considerable progress has been made in the treatment of CRC in recent years12. Thus far, 5-fluorouracil (5-FU) remains a widely used chemotherapeutic drug in the treatment of various cancers, including colorectal carcinoma, breast cancer, gastric cancer and other solid tumors.…”
mentioning
confidence: 99%
“…Colorectal cancer (CRC) is still a leading cause of cancer-related morbidity and mortality around the world, although a lot of progress has been made in the treatment of CRC over the past years [1], [2]. Epidemiologic studies have shown that diabetes mellitus (DM) increases incidence and mortality of cancers, especially gastrointestinal malignancy [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…This might indicate the importance of APC inactivation in tumorigenesis of these organs [31]. Moreover, recent reports indicate that APC is an important prognostic indicator for unfavorable clinicopathological outcome and tumor recurrence in several types of cancers [29,30].…”
Section: Introductionmentioning
confidence: 99%